Mechanical testing of orthopaedic suture material and a crimp clamp system for the extracapsular stabilisation of canine cruciate-deficient stifles - V. Ledecky; D. Knazovicky; M. Badida; L. Dulebova; M. Hluchy; S. Hornak (Veterinární Medicína, 2012)
The cranial cruciate ligament (CCL) provides cranio-caudal stability, prevents hyperextension and constrains medial rotation of the tibia in the canine stifle joint and CCL rupture is the leading cause of hind leg lameness in dogs. Treatment of CCL rupture aims to resolve lameness caused by joint instability and provide good long-term function of the affected hind limb. The extracapsular technique is one of the most popular methods to restore joint stability. The technique involves a suture loop that is placed around the lateral fabella and through the tibial tuberosity. The ideal suture material should be strong, aseptic, easily handled, inexpensive, and provide excellent knot security and knot compactness. A critical property of the loop is the application of either a knot or crimp to maintain the tension on the loop. There is a variety of orthopaedic suture materials used for the extracapsular technique. Our aim was to compare the mechanical properties of four commercially available materials in pure tension. The materials tested were monofilament nylon leader (MNL) 100 lb, MNL 80 lb, Supramid and Silon. Our second objective was to compare the interoperator variability of applying either a knot or a crimp to secure the suture loop. Ultimate tensile strength was greatest with MNL 100 lb (373 N) followed by MNL 80 lb (285 N), Supramid (160 N) and Silon (103 N). Based on our results, we conclude that MNL 100 lb and MNL 80 lb are mechanically superior to Silon and Supramid. Our study also shows significant effects for the operator and method of loop fixation (P < 0.0001). Intraoperator differences were also found to be significant, for operator 1 (P < 0.0001), for operator 2 (P < 0.001) and operator 3 (P < 0.01). Our findings indicate that MNL is most suitable orthopaedic material and that loop fixation should remain the method of choice for surgeons treating CCL.